Driverless simulation of path tracking based on PID control. Issue 1 (July 2020) - Wang, Zhaojian; Wang, Mengen; Zhang, Yaoming; Guan, Tian; Song, Xiaoli; Liu, Jiawei; Zhen, Yajing; Zhang, Dongsheng
Abstract: In order to realize the path tracking of autonomous vehicles, this paper first simplifies the complex structure of the vehicle into a two-degree-of-freedom kinematic and dynamic vehicle model. based on PID control, the vehicle path tracking controller is designed to calculate the lateral deviation between the expected path and the actual path, and outputs the front wheel rotation angle through the controller, so that the autonomous vehicle can travel well according to the expected path. The control system model is built in the MATLAB/Simulink, and the vehicle path tracking control system is simulated and verified jointly with the CarSim software platform. Simulation results show that the designed control strategy can ensure the path tracking performance of intelligent vehicles at different speeds, and has good tracking accuracy, real-time performance and vehicle driving stability.